5'-structural analysis of genes encoding polymorphic antigens of chemically induced tumors. - Srivastava, P K (1987)
We have proposed that the distinct tumor rejection antigens of chemically induced sarcomas in inbred mice belong to a family of Mr 96,000 glycoproteins (gp96). An identical 14-amino acid sequence was found at the amino terminus of gp96 from two antigenically distinct BALB/c sarcomas. Oligonucleotide probes derived from this sequence permitted isolation of 5' cDNA and genomic fragments coding for gp96. Three short exons interrupted by relatively long introns were identified at the 5' terminus of the gp96 gene. The first exon encodes a signal peptide, which is consistent with gp96 being a cell surface antigen. Southern blot analysis indicated that the gp96 family is encoded by a single gene, and 3-kilobase transcripts were detected in all normal and tumor cells tested. Nucleotide and deduced amino acid sequences from 311 base paris at the 5' terminus showed no homology with any known protein. The availability of molecular probes for the gp96 system permits analysis of the structural polymorphism of these antigens.